Behaviour and ability of a cyprinid (Schizopygopsis younghusbandi) to cope with accelerating flows when migrating downstream. (22nd July 2020) - Li, Minne; Shi, Xiaotao; Jin, Zhijun; Ke, Senfan; Lin, Chenyu; An, Ruidong; Li, Jia; Katopodis, Christos
Abstract: The migration corridors in regulated rivers lead downstream fish migrants, particularly juveniles to pass through water infrastructure. Accelerating flow, experienced by fish, might trigger avoidance behaviour and then influence the downstream migration efficacy. It is essential to understand the causes of avoidance behaviour exhibited by downstream migratory fish in accelerating flow. In this study, the effect of three different accelerating flows on the downstream migration behaviour of Schizopygopsis younghusbandi ( S.Y ) was investigated using a constriction wedge in a circulating flume. The results showed that some fish (30%, 23%, and 39% under low, medium, and high flow conditions, respectively) repeatedly attempted to burst upstream with positive rheotaxis prior to successful passage downstream. Under the low‐, medium‐, and high‐accelerating levels, the average fish swimming speeds were 89.19, 91.28, and 111.94 cm/s, respectively; these values were close to the critical swimming speed (110.42 cm/s) of the target fish. The water velocities at the fish avoidance points were centrally distributed at approximately 73.03 cm/s. Regarding turbulence, the results exhibited that the S.Y generally responded to a discrete range of <50 cm 2 /s 2 of turbulent kinetic energy and < 2 N/m 2 of the horizontal component of the Reynolds shear stress (RSSxy ). Also, the fish that exhibited avoidance behaviour were not centrally distributed in the lateral and longitudinal velocity locations, where there was an abrupt change in the gradient. This study highlighted the impact of accelerating flow on the downstream fish migration behaviour of a cyprinid. Furthermore, this study quantified the hydraulic factors that triggered this avoidance. Thus, it provided experimental support for optimizing the design of the hydraulic factors for downstream fishways.